Chromium-doped ferro-nickel sulfide nanorod array material, preparation method thereof and application of chromium-doped ferro-nickel sulfide nanorod array material in seawater electrolysis oxygen evolution

By growing chromium-doped nickel-ferrous sulfide nanorod array material on foam nickel-iron foam substrate, the problems of anode corrosion and insufficient catalyst stability in electrolytic seawater are solved, and efficient electrolytic seawater oxidation performance and long-term stable operation are achieved.

CN119243234APending Publication Date: 2025-01-03HAIHYDR TECHNOLOGY (WUHAN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411349910.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-12
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing hydrogen production technology of electrolytic seawater, chloride ions in seawater cause anode corrosion, limiting the long-term stability of electrolytic seawater. In addition, precious metal-based catalysts have high prices and limited reserves, nickel-iron-based electrocatalysts have the performance of alkaline seawater electrolysis and Inadequate stability.

Method used

Using chromium-doped nickel-iron sulfide nanorod array material as oxidation electrode, the nanorod array structure is prepared by hydrothermal method to improve catalytic activity and stability.

Benefits of technology

It significantly improves the oxidation performance, catalytic activity and stability of electrolytic seawater, can run for a long time at high current density without attenuation, provides excellent overpotential and electrical conductivity, and reduces the risk of anode corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062053170000061
    Figure BDA0005062053170000061
  • Figure HDA0005062053200000011
    Figure HDA0005062053200000011
  • Figure HDA0005062053200000012
    Figure HDA0005062053200000012
Patent Text Reader

Abstract

The invention belongs to the field of catalysts for oxygen production through seawater electrolysis, and particularly discloses a chromium-doped ferronickel sulfide nanorod array material, a preparation method thereof and application of the chromium-doped ferronickel sulfide nanorod array material to oxygen evolution through seawater electrolysis. The material is a chromium-doped ferronickel sulfide grown in situ on a foamed ferronickel substrate, has components of NiFe, Ni3S2 and (Fe, Ni) 3S4, and is of a nanorod array structure. The preparation method comprises the following steps: putting the cleaned foam ferronickel into a solution containing a sulfur source and chromate, and obtaining the chromium-doped ferronickel sulfide nanorod array material by utilizing a hydrothermal method. As an alkaline water and seawater oxidation electrode, the composite material shows extremely excellent catalytic activity and stability, and has potential application value in the aspect of developing a transition metal OER catalyst for electrolyzing seawater to evolve oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts for electrolyzing seawater to produce oxygen, and specifically relates to a chromium-doped nickel-iron sulfide nanorod array material, a preparation method thereof, and an application of electrolyzing seawater to produce oxygen. Background Art

[0002] Among various renewable energy sources, hydrogen is regarded as an ideal energy source with broad prospects due to its high energy density, simple chemical composition and environmentally friendly properties. However, the production method of hydrogen is the main factor restricting its development. At present, hydrogen production technology mainly includes the use of fossil fuels, biomass and water electrolysis to produce hydrogen. In particular, water electrolysis hydrogen production technology has attracted much attention due to its advantages of environmental protection, sustainability and easy industrialization. However, global freshwater resources only account for about 3.5% of total water resources. If freshwater electrolysis is used on a large scale to produce hydrogen, it will further aggravate the problem of global freshwater resource shortage. Considering that the earth has abundant seawater resources, seawater electrolysis to produce hydrogen is regarded as one of the important directions for the future development of hydrogen energy. However, there are many challenges in the electrolysis of seawater. Seawater is rich in chloride ions (Cl - ), during the electrolysis of seawater, highly oxidizing hypochlorite will be generated, which will corrode the anode and hinder the long-term stability of electrolyzed seawater. According to research, the thermodynamic potential of the oxygen evolution reaction (OER) in alkaline seawater is 490mV lower than that of the chlorine evolution reaction (CER), so highly active anode catalysts can limit the chlorine reaction, reduce anode corrosion, and facilitate the stable electrolysis of seawater. Therefore, designing highly active, highly selective, chloride-resistant and highly stable anode catalysts for electrolysis of seawater is crucial to promote the development of the electrolysis of seawater industry.

[0003] As we all know, precious metal-based catalysts (such as IrO2 and RuO2) have difficulties in widespread application due to their high price, limited reserves and insufficient stability. In recent years, nickel-iron-based electrocatalysts have been widely regarded as having broad application prospects due to their advantages such as low price, abundant reserves and excellent performance in OER. However, their performance and stability in alkaline seawater electrolysis still need to be improved. Summary of the invention

[0004] The purpose of the present invention is to provide a chromium-doped nickel-iron sulfide nanorod array material and its preparation method and application in electrolyzing seawater for oxygen evolution in view of the problems existing in the prior art. As an alkaline water and seawater oxidation electrode, it has excellent catalytic activity and stability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A chromium-doped nickel-iron sulfide nanorod array material is a chromium-doped nickel-iron sulfide in-situ grown on a nickel-iron foam substrate, has NiFe, Ni3S2 and (Fe, Ni)3S4 components, and presents a nanorod array structure.

[0007] According to the above scheme, the chromium atom content in the chromium-doped nickel-iron sulfide nanorod array material is 0.55 at% to 3.75 at%, the iron atom content is 7.18 at% to 10.11 at%, the nickel atom content is 41.24 at% to 48.52 at%, and the sulfur atom content is 42.38 at% to 48.10 at%.

[0008] According to the above scheme, the doping amount of chromium atoms in the chromium-doped nickel-iron sulfide nanorod array material is 2.07

[0009] at%-3.75at%.

[0010] According to the above scheme, the width of the nanorod is 60-100 nm.

[0011] The second aspect of the present invention provides a method for preparing a chromium-doped nickel-iron sulfide nanorod array material, comprising the following steps: placing cleaned nickel-iron foam in a solution containing a sulfur source and chromate, and preparing the chromium-doped nickel-iron sulfide nanorod array material by a hydrothermal method.

[0012] According to the above scheme, the sulfur source material is thiourea, thioacetamide or sodium sulfide.

[0013] According to the above scheme, the concentration of the sulfur source solution is 0.05-0.25 mol / L.

[0014] According to the above scheme, the hydrothermal conditions in the hydrothermal method are 120-220° C. and the hydrothermal time is 4-24 hours.

[0015] According to the above scheme, the chromate is Na2CrO4, K2CrO4 or (NH4)2CrO4.

[0016] According to the above scheme, the concentration of the chromate solution is 0.008-0.075 mol / L.

[0017] The third aspect of the present invention provides the use of the chromium-doped nickel-iron sulfide nanorod array material in the electrolysis of alkaline water or seawater for oxygen evolution.

[0018] The present invention provides a chromium-doped nickel-iron sulfide, which is a chromium-doped nickel-iron sulfide nanorod array grown on a nickel-iron foam substrate, which can fully expose active sites, and the introduction of chromium improves the conductivity and causes the charge around the iron atoms and the nickel atoms to be redistributed, and the high-valent Fe 3+ and Ni3+ It can be increased, which greatly promotes the reaction kinetics of oxygen evolution reaction in seawater electrolysis, improves the OER activity of the catalyst, and ultimately significantly improves the seawater oxidation performance of the electrode.

[0019] Beneficial effects of the present invention:

[0020] 1. The chromium-doped nickel-iron sulfide nanorod array material provided by the present invention exhibits excellent catalytic activity and stability as an alkaline water and seawater oxidation electrode, and has potential application value in the development of transition metal OER catalysts for electrolysis of seawater for oxygen evolution. 2 At a current density of 500 mA / cm, the overpotentials required in alkaline aqueous solution were as low as 173, 211, and 253 mV, and the overpotentials required in alkaline seawater were 190, 231, and 271 mV. 2 It can run for up to 1000 hours at a constant current density without obvious attenuation of seawater oxidation performance, and its performance is excellent.

[0021] 2. The present invention uses nickel iron foam as a substrate, and adopts a hydrothermal method in a solution containing a sulfur source to achieve controllable synthesis of chromium-doped nickel iron sulfide materials with a nanorod array structure in the presence of chromate. The synthesized chromium-doped nickel iron sulfide nanorod array material exhibits excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ) Scanning electron microscope (SEM) images at different magnifications;

[0023] Figure 2 The scanning electron microscope (SEM) images of nickel iron sulfide (denoted as NiFeSx) at different magnifications;

[0024] Figure 3 Cr-NiFeS x Distribution diagram of Cr, Fe, Ni and S elements;

[0025] Figure 4 (a) is Cr-NiFeS x X-ray diffraction pattern (XRD); (b) Cr-NiFeS x Raman spectrum of Cr-NiFeS x (d) Ni 2p energy level diagram of X-ray photoelectron spectroscopy (XPS); (e) Cr-NiFeS x XPS Fe 2p energy level diagram;

[0026] Figure 5 Cr-NiFeS x Comparison of OER performance with other samples in alkaline aqueous electrolyte (1 mol / L potassium hydroxide); (a) linear sweep voltammetry (LSV) curve; (b) comparison of overpotentials at different current densities; (c) Tafel slope plot; (d) electrochemical impedance spectroscopy (EIS);

[0027] Figure 6 Cr-NiFeS x Comparison of OER performance with other samples in alkaline seawater electrolyte (1 mol / L potassium hydroxide + seawater); (a) linear sweep voltammetry (LSV) curve; (b) overpotential comparison at different current densities; (c) at 500 mA / cm 2 Performance curves for stable testing at current density. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] Example 1

[0030] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0031] An embodiment of the present invention provides chromium-doped nickel-iron sulfide, in which a chromium-doped nickel-iron sulfide nanorod array is grown on a nickel-iron foam substrate by a one-step hydrothermal method.

[0032] The present invention also discloses a preparation method, the steps of which are as follows:

[0033] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.2 mol / L thiourea and 0.05 mol / L Na2CrO4, and reacted at 200°C for 12 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0034] (2) The prepared Cr-NiFeS x A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0035] Control: Step (1) without adding Na2CrO4, synthesizing NiFeS x .

[0036] Figure 1 Cr-NiFeS x SEM images at different magnifications show that Cr-NiFeS x It presents a densely distributed nanorod array morphology, with a length of about 800 to 1200nm, and even longer, such as 1um, 2um, 3um, etc.

[0037] Figure 2 NiFeS x SEM images at different magnifications show that NiFeS without Cr doping x , showing only a bulk stacking morphology. The controllable synthesis of chromium-doped nickel-iron sulfide materials with nanorod array structures was achieved in the presence of chromate.

[0038] Figure 3 Cr-NiFeS x According to the EDS test results, Cr, Fe, Ni and S elements are evenly distributed, with the chromium atom content of 2.07at%, the iron atom content of 9.68at%, the nickel atom content of 45.57at% and the sulfur atom content of 42.68at%.

[0039] Figure 4 (a) XRD pattern of Cr-NiFeS x The characteristic peaks match those of (Ni,Fe) (PDF#12-0736), Ni3S2 (PDF#02-0722), and (Fe,Ni)3S4 JCPDS#11-095. Figure 4 (b) Cr-NiFeS x The Raman spectrum of the metal-sulfur nanostructured carbon nanotubes showed obvious characteristic signals. Figure 4 (c) shows the two samples (NiFeS obtained by direct hydrothermal sulfidation of nickel-iron foam) x and Cr-NiFeS x )XPS Ni 2p level spectrum comparison, NiFeS x Catalyst Ni 3+ with Ni 2+ The peak area is 0.435:1, while Cr doped into NiFeS x Cr-NiFeS x Chinese Ni 3+ with Ni 2+ The peak area increased to 0.667:1. Figure 4 (d) The XPS Fe 2p level spectra of the two samples also show similar patterns. x Cr-NiFeSx Fe 3+ with Fe 2+ The peak area increased from the original 1.125:1 to 1.365:1. This is because the introduction of Cr caused the charge around Ni atoms and Fe atoms to be redistributed. 3+ and Fe 3+ The high-valent Ni and Fe are often important active sites in the OER reaction process, thus improving the OER activity of the catalyst.

[0040] Figure 5 (a) and (b) show NiFeS x 、Cr-NiFeS x The linear sweep voltammetry (LSV) curves of the commercial RuO2 sample in 1 mol / L potassium hydroxide solution and the detailed OER overpotential comparison diagram can be found. x Excellent ORER performance: 10, 100 and 500 mA / cm 2 At a current density of 1.34 W, the overpotential required in alkaline aqueous solution is as low as 173, 211 and 253 mV, which is much better than the commercial RuO2 samples. The Tafel slopes of these samples are further calculated as Figure 5 (c) shows that Cr-NiFeS x The sample has a low Tafel slope of 37.90 mV / dec. In addition, Figure 5 (d) Electrochemical impedance spectroscopy of Cr-NiFeS x The smaller charge transfer resistance reflects that the Cr-NiFeS x It has better conductivity, thus promoting rapid electron transfer on the catalyst.

[0041] Figure 6 The electrochemical performance test results of the samples in alkaline seawater electrolyte (1 mol / L potassium hydroxide + seawater) are shown. Figure 6 (a) and (b) show NiFeS x and Cr-NiFeS x LSV curves of samples in alkaline seawater electrolyte and comparison of overpotentials at different current densities. x The samples have excellent OER performance in alkaline seawater at 10, 100 and 500 mA / cm 2 At current densities of , the required OER overpotentials are only as low as 190, 231, and 271 mV, as shown in Table 1. Figure 6 (c) shows the stability test results of NiFeSx at 500mA / cm2 The current density can only run for about 10 hours, while the Cr-NiFeS nanorod array structure of the present invention x Sample at 500mA / cm 2 It can run stably for 1000 hours at a constant current density without obvious performance degradation.

[0042] Example 2

[0043] The chromium-doped nickel-iron sulfide provided in one embodiment of the present invention grows a chromium-doped nickel-iron sulfide nanorod array on a nickel-iron foam substrate by a one-step hydrothermal method, wherein the chromium atom content is 1.04 at%, the iron atom content is 7.41 at%, the nickel atom content is 43.98 at%, and the sulfur atom content is 47.57 at%. The present embodiment also discloses a preparation method, and the steps of the method are as follows:

[0044] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.25 mol / L sodium sulfide and 0.015 mol / L K2CrO4, and reacted at 220°C for 8 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0045] (2) The prepared Cr-NiFeS x A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0046] Example 3

[0047] An embodiment of the present invention provides a chromium-doped nickel-iron sulfide, in which a chromium-doped nickel-iron sulfide nanorod array is grown on a nickel-iron foam substrate by a one-step hydrothermal method, wherein the chromium atom content is 0.55 at%, the iron atom content is 10.11 at%, the nickel atom content is 41.24 at%, and the sulfur atom content is 48.10 at%.

[0048] The present invention also discloses a preparation method, the steps of which are as follows:

[0049] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.15 mol / L thioacetamide and 0.008 mol / L (NH4)2CrO4, and reacted at 120°C for 24 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0050] (2) The prepared Cr-NiFeS x A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0051] Example 4

[0052] An embodiment of the present invention provides a chromium-doped nickel-iron sulfide, in which a chromium-doped nickel-iron sulfide nanorod array is grown on a nickel-iron foam substrate by a one-step hydrothermal method, wherein the chromium atom content is 3.75 at%, the iron atom content is 8.99 at%, the nickel atom content is 44.12 at%, and the sulfur atom content is 43.14 at%.

[0053] The present invention also discloses a preparation method, the steps of which are as follows:

[0054] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.10 mol / L thiourea and 0.075 mol / L Na2CrO4, and reacted at 180°C for 4 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0055] (2) The prepared Cr-NiFeS x A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0056] Example 5

[0057] An embodiment of the present invention provides a chromium-doped nickel-iron sulfide, in which a chromium-doped nickel-iron sulfide nanorod array is grown on a nickel-iron foam substrate by a one-step hydrothermal method, wherein the chromium atom content is 2.52 at%, the iron atom content is 8.31 at%, the nickel atom content is 46.77 at%, and the sulfur atom content is 42.40 at%.

[0058] The present invention also discloses a preparation method, the steps of which are as follows:

[0059] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.18 mol / L sodium sulfide and 0.06 mol / L K2CrO4, and reacted at 140°C for 16 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0060] (2) The prepared Cr-NiFeSx A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0061] Example 6

[0062] An embodiment of the present invention provides a chromium-doped nickel-iron sulfide, in which a chromium-doped nickel-iron sulfide nanorod array is grown on a nickel-iron foam substrate by a one-step hydrothermal method, wherein the chromium atom content is 0.82 at%, the iron atom content is 7.18 at%, the nickel atom content is 48.52 at%, and the sulfur atom content is 43.48 at%.

[0063] The present invention also discloses a preparation method, the steps of which are as follows:

[0064] (1) The cleaned nickel-iron foam was placed in a 60 mL solution containing 0.05 mol / L thioacetamide and 0.001 mol / L (NH4)2CrO4, and reacted at 16°C for 10 h using a hydrothermal method. After the reaction was completed and cooled to room temperature, it was rinsed and dried in an oven to obtain chromium-doped nickel-iron sulfide (denoted as Cr-NiFeS x ).

[0065] (2) The prepared Cr-NiFeS x A three-electrode system consisting of a working electrode, a mercury oxide electrode as a reference electrode and a graphite rod electrode as a counter electrode was placed in an alkaline seawater solution to test its seawater oxidation performance.

[0066] Table 1 Cr-NiFeS prepared in different embodiments x Summary of alkaline seawater oxidation performance of samples

[0067]

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A chromium-doped nickel-iron sulfide nanorod array material, characterized in that: The material is a chromium-doped nickel-iron sulfide grown in situ on a nickel-iron foam substrate, having NiFe, Ni3S2 and (Fe, Ni)3S4 components and presenting a nanorod array structure.

2. The nickel-iron sulfide nanorod array material according to claim 1, characterized in that: The chromium atom content of the chromium-doped nickel-iron sulfide nanorod array material is 0.55 at% to 3.75 at%, the iron atom content is 7.18 at% to 10.11 at%, the nickel atom content is 41.24 at% to 48.52 at%, and the sulfur atom content is 42.38 at% to 48.10 at%.

3. The nickel-iron sulfide nanorod array material according to claim 1, characterized in that: The doping amount of chromium atoms in the chromium-doped nickel-iron sulfide nanorod array material is 2.07 at%-3.75 at%.

4. The method for preparing the chromium-doped nickel-iron sulfide nanorod array material according to claim 1, characterized in that: The following steps are involved: The cleaned nickel-iron foam is placed in a solution containing a sulfur source and chromate, and a chromium-doped nickel-iron sulfide nanorod array material is prepared by a hydrothermal method.

5. The preparation method according to claim 4, characterized in that: The sulfur source material is thiourea, thioacetamide or sodium sulfide.

6. The preparation method according to claim 4, characterized in that: The concentration of the sulfur source solution is 0.05-0.25 mol / L.

7. The preparation method according to claim 4, characterized in that: The hydrothermal method has a hydrothermal condition of 120 to 220° C. and a hydrothermal time of 4 to 24 hours.

8. The preparation method according to claim 4, characterized in that: The chromate is Na2CrO4, K2CrO4 or (NH4)2CrO4.

9. The preparation method according to claim 4, characterized in that: The concentration of the chromate solution is 0.008-0.075 mol / L.

10. Use of the chromium-doped nickel-iron sulfide nanorod array material according to claim 1 in electrolysis of alkaline water or seawater for oxygen evolution.

Citation Information

Cited By

  • Method for in-situ preparation of Ni-Fe7S8 / MoS2 heterojunction nano material based on iron foam and application

    CN120205236A